Interactive Multimedia Learning : Using Social Media for Peer Education in Single-Player Educational Games - Konert, Johannes (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2015)
This book introduces new concepts and mechanisms regarding the usage of both social media interactions and artifacts for peer education in digital educational games. Digital games in general, and digital educational games in particular, represent an area with a high potential for interdisciplinary innovation, not only from an information technology standpoint, but also from social science, psychological and didactic perspectives. This book presents an interdisciplinary approach to educational games, which is centered on information technology and aims at: (1) improving digital management by focusing on the exchange of learning outcomes and solution assessment in a peer-to-peer network of learners; (2) achieving digital implementation by using forms of interaction to change the course of educational games; and (3) providing digital support by fostering group-formation processes in educational situations to increase both the effects of educational games and knowledge exchange at the individual level. In addition to a systematic analysis of the relationship between software architecture, educational games and social media applications, the book also presents the implemented IT systems' architectures and algorithmic solutions as well as the resulting applicable evaluation findings from the field of interactive multimedia learning.